Analisis Tingkat Kepuasan Kerja Pegawai pada PT. Kereta Api Indonesia (Persero) Unit Sarana Depo Kereta Bandung - Fadilah, Bunga Sri; Dewi, Lies Anggi Puspita (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This study aims to analyze the level of employee job satisfaction at PT. Kereta Api Indonesia (Persero) Unit Sarana Depo Kereta Bandung. The method used in this research is qualitative descriptive method, namely the method of analyzing and classifying or compiling data in such a way that the results of measuring variables are operationalized using numbers so that they can be examined based on theories that are closely related to the problems discussed. The respondents in this study were all employees of PT. Kereta Api Indonesia (Persero) Unit Sarana Depo Kereta Bandung. From the results of research that has been done by the author obtained the answer that employee job satisfaction at PT. Kereta Api Indonesia (Persero) Unit Sarana Depo Kereta Bandung is in the sufficient category. Where from the respondent’s part assess indicators such as the job itself, salary, cowokers, superiors, promorions and a supportive work environment and can increase effectiveness and job satisfaction.